PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PEREDARAN KOSMETIK YANG BERBAHAYA (Studi Kasus Badan Pengawas Obat dan Makanan di Buleleng) - Lucky Rahul Ferdian; Komang Febrinayanti Dantes; Si Ngurah Ardhya (Universitas Pendidikan Ganesha, 2023)
This study aims to examine and analyze consumer legal protection against the circulation of cosmetics that harm consumers as well as examine and analyze the role and responsibilities of BPOM in order to provide consumer protection for the distribution of cosmetics in Buleleng district. The type of research used is Empirical Legal Research. Data and data sources used are primary data and secondary data. Data collection techniques used are library research, interviews, and field studies. The sampling technique used was purposive sampling. Furthermore, the data obtained was processed and analyzed qualitatively. The results of the study show that preventive and law enforcement measures are taken to protect consumers from dangerous cosmetic products circulating without a distribution permit. These efforts include communication, education, inspection, prosecution, and cooperation with various related parties. In dealing with business actors who sell dangerous products, BPOM takes actions ranging from warnings to more stringent actions such as coaching and courts.